Perspektif Wajib Pajak Terkait Surat Permintaan Penjelasan Data dan/atau Keterangan di Kantor Pelayanan Pajak Pratama Makassar Utara - Riswanto Mongka; Mursalim Laekkeng; Abbas Selong (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The research aims to understand the experiences and views of taxpayers regarding the Request for Data and/or Information Explanation Letters (SP2DK). Using a phenomenological approach, the study found that taxpayers' experiences with SP2DK reflect mixed feelings of caution and hope for a fair resolution. Most taxpayers perceive SP2DK as a form of audit or investigation that increases administrative burdens and raises concerns about potential sanctions. However, some taxpayers view SP2DK as an opportunity to provide clarification and demonstrate their tax compliance. Generally, taxpayers expect the clarification process to be transparent, clear, and fair, enabling tax issues to be resolved without causing further uncertainty.